Manajemen Pemasok Pada Rantai Pasokberjaringberas Di Desa Pematang Johar, Kecamatan Lebuhan Deli, Kabupaten Deli Serdang - Lubis, Aulia Azmi; Viantika, Dinda Savira; Aisyah, Siti (Universitas Labuhanbatu, 2022)
In Indonesia, there is no doubt about its biological results. To guarantee its food ingredients, Indonesia is also known for its biological source, namely rice. Rice is one of the main staple foods and is mandatory for Indonesians. Food is also something that is either processed or unprocessed, which is specifically designated as food and drink for human consumption. Based on research by the Food Security Agency (2018) which states that districts/cities can be classified into 6 groups for food and nutrition security based on the severity and causes of food and nutrition security, namely priority 1 (high food insecurity), priority 2 (food insecurity). medium), priority 3 (low food insecurity), priority 4 (low food security), priority 5 (medium food security) and priority 6 (high food security). This study looks directly at the production and income of partner rice and non-partner farmers in Deli Serdang Regency. By using income analysis, it is known that the partnership in increasing the production and income of the rice business. Partnerships are able to improve the bargaining position of farmers through obtaining higher prices and market certainty.